Multiple clinically relevant immunotherapies prolong the function of microencapsulated porcine islet xenografts in diabetic NOD mice without the use of anti‐CD154 mAb. (6th January 2020) - Safley, Susan A.; Barber, Graham F.; Holdcraft, Robert W.; Gazda, Lawrence S.; Duncanson, Stephanie; Poznansky, Mark C.; Sambanis, Athanassios; Weber, Collin J.
Abstract: Background: Our goal was to identify clinically relevant immunotherapies that synergize with microencapsulation to protect adult porcine islet (API) xenografts in diabetic NOD mice. We have shown previously that dual costimulatory blockade (CTLA4‐Ig plus anti‐CD154 mAb) combined with encapsulation protects APIs long‐term in NOD mice. Since no anti‐CD154 mAbs currently are approved for use in humans, we tested the efficacy of other targeted immunosuppression regimens that might be used for diabetic patients receiving encapsulated islets. Methods: Microencapsulated APIs were transplanted i.p. in diabetic NOD mice given either no immunosuppression or combinations immunosuppressive reagents. Graft function was monitored by blood glucose levels, i.p. glucose tolerance tests, and histology. Mechanisms of rejection were investigated by phenotyping host peritoneal cells and measuring graft site cytokine and chemokine levels. Results: New immunosuppressive therapies were compared to CTLA4‐Ig plus anti‐CD154 mAb, used here as a control. The most effective was triple treatment with CTLA4‐Ig, anti‐CD154 mAb, and intracapsular CXCL12, and the next most effective was a non‐depleting anti‐CD4 mAb (YTS177.9) plus intracapsular CXCL12. Three additional regimens (CTLA4‐Ig plus YTS177.9, YTS177.9 alone, and anti‐OX40‐Ligand mAb alone) significantly prolonged encapsulated API function. Dual treatment with CTLA4‐Ig plus anti‐CD40 mAb was as effective as CTLA4‐Ig plus anti‐CD154 mAb. Five other monotherapies and three combination therapies did not augment encapsulated API survival. Most peritoneal cytokines and chemokines were either absent or minimal. At necropsy, the capsules were intact, not fibrosed, and clean when function was maintained, but were coated with host cells if rejection had occurred. Conclusions: Multiple different immunotherapies which specifically inhibit CD4 + T cells, modulate T‐cell trafficking, or interfere with antigen presentation can substitute for anti‐CD154 mAb to prolong encapsulated islet xenograft function in diabetic NOD mice.